Uso de biossorventes no tratamento de águas: uma sequência didática em química ambiental - Guimarães, Barbara Queiroz (2021)
This work presents the improvement of a Didactic Sequence (DS) developed on two distinct occasions in the environmental chemistry discipline offered in the chemistry graduation of a public university. The first occasion was realized in a presential format, where was prepared biosorbents from papaya peel and acerola residue. The biosorbents were characterized by Fourier Transform Infrared Spectroscopy, Scanning Electron Microscopy, and determination of the Point of Zero Charge. The adsorption capacity was available experimentally by the students. A DS was developed for the wastewater treatment approach and the use of biosorbent. The Didactic Sequence was divided into Three Pedagogical Moments (3PM): Problematization and Contextualization (P e C), was approached the water bodies' contamination; in Knowledge Organization (KO) when conducting research, and debates on the use of biosorbents; in Knowledge Application (KA) were accomplishing an experimental class using the CM and AR biosorbents in the biosorption of methylene blue dye. To evaluate the adsorbent potential of the materials in the dye removal as a function of the pH (3,0; 6,0; 9,0) was made the measure of absorption using a spectrophotometer (665 nm) and the concentration using a cellphone. The results suggest that the RA biosorbent presented the best adsorptive capacity when compared to CM. Because of the new coronavirus pandemic, the education project was developed remotely, where the students used homemade resources for biosorption preparation and testing. In the P was presented scientific research about the removal of contaminants using biosorbents. The KO was introduced video lessons about biosorbent materials and their characteristics and was made virtual meetings to keep up with the student's material production. In KA, students prepared and tested the biosorbent material and presented the results to the class. Thus, it was possible to mediate knowledge about the biosorbents use, besides encouraging the different forms of production of this material, exploring the creative capacity, and the search for environmental problems solutions.